Paradoxical puborectalis contraction is a feature of constipation in patients with multiple sclerosis. - Chia, Y W (1996)
OBJECTIVE--To study the disturbed anorectal physiology associated with constipation in multiple sclerosis. METHODS--Anorectal function in 10 patients with clinically definite multiple sclerosis and constipation has been compared with 10 normal persons and 11 patients with idiopathic constipation, without multiple sclerosis. RESULTS--All 10 constipated patients with multiple sclerosis had difficulty evacuating barium paste during defaecography. In four of these there was complete failure of puborectalis relaxation when straining to defaecate, and in another four there was incomplete puborectalis relaxation. There was no evidence of lower motor neuron involvement of pelvic floor muscles in the multiple sclerosis group. CONCLUSIONS--Paradoxical puborectalis contraction is common in patients with multiple sclerosis in whom constipation is a symptom. This may be a feature of the disturbed voluntary sphincter control mechanism, analogous to detrusor sphincter dyssnergia in the bladder.